Analisis Keunikan Produk dan Inovasi Produk Terhadap Kinerja Pemasaran Melalui Keunggulan Bersaing pada Busana Muslim di Surabaya - Sisilia Suci Yunitasari Suci Yunitasari; Muhadjir Anwar (Widya Manajemen, 2022)
This study aims to identify and examine product uniqueness and product innovation on marketing performance through competitive advantage in Muslim clothing in Surabaya. Structural equation modeling is used to test research hypotheses on the database of Muslim fashion brands in Surabaya. Data were taken from the responses of 65 respondents; Questionnaires were distributed to owners or business managers of Muslim fashion brands in Surabaya. The findings show that the uniqueness of the ability to create unique products for Muslim clothing products brings huge benefits in improving marketing performance. and enable the development and attraction of customers in the Muslim fashion brand business to get bigger. By reviewing various pieces of literature on views based on product uniqueness, product innovation, competitive advantage, and marketing performance, this study offers an analysis of product uniqueness and product innovation on marketing performance through competitive advantage in Muslim fashion brands which have received a lot of attention from researchers. Conceptual discussion and empirical results expand on previous research on marketing performance and competitive advantage based on product uniqueness and product innovation.